Resilience Enhancement and Evaluation Methods for Space–Air–Ground Integrated Networks - Zhenyu Xiao; Bangwen Chen; Tianqi Mao; Zhu Han (Space: Science & Technology)
Space–air–ground integrated networks (SAGINs) have been considered to be the trend of future 6G network development. In the presence of hostile interferers/attackers especially under military application scenarios, the resilience of the SAGIN to various threats such as physical, electronic, and cyberattacks can be crucial to guarantee desirable networking performance. This motivates advanced enhancement and evaluation schemes for the resilience of SAGIN. In this paper, the SAGIN resilience enhancement process is divided into 4 resilience enhancement phases, namely, resistance, absorption, recovery, and reconfiguration. Then, different resilience enhancement methods are discussed and analyzed within each phase, respectively. Further, considering that SAGIN is coupled by several cross-domain subsystems, the indicator system for resilience capabilities evaluation and evaluation methods of SAGIN are given. Firstly, the resilience capability of each subsystem is evaluated based on 4 indicators, namely, resistance, absorption, recovery, and reconfiguration capability. Then, by combining the resilience capability of the space-based, air-based, and ground-based communication subnetworks, the overall resilience enhancement capability of SAGIN is evaluated.